Low toxicity mechanistic insights into Z-scheme WO3/BiFeO3/DSB photocatalysts for efficient ampicillin degradation - Junxin Yu; Tianyu Gu; Ruiying Wang; Xiaohui Zhu; Zhexuan Li; Weiming Zhu; Li Jiang; Zhiying Dong; Bing Li (npj Clean Water)
Abstract Ampicillin (AMP) poses a significant environmental hazard to aquatic ecosystems, and previous research has been inadequate in addressing the ecological toxicity of its byproducts. A novel photocatalyst, WO3-BiFeO3/digestate biochar (DSB), denoted WBD, was synthesized for efficient photocatalytic degradation of AMP. In our study, 150 mg WBD achieved 99.93% AMP degradation in 3 h at a concentration of 100 mg/L. WBD maintained a stable degradation performance under various environmental stressors, including pH, and the presence of Cl−, NO3 −, and HA. •O2 −, h+, •OH, and 1O2 were identified as primary active oxygen species. WBD effectively targeted the -NH2, -SH, and β-lactam ring-forming -COOH of AMP, facilitating its transformation into low-toxic or non-toxic degradation products, and establishing a detoxification pathway. Overall, this study introduces a novel environmentally material that demonstrates a high degradation efficiency, long-lasting effectiveness, and low product toxicity, offering a promising approach for the effective management of emerging pollutants.